EKSOTISME PAKISTAN DAN INDIA DALAM “THE HOLY WOMAN” DAN “TYPHOON” KARYA QAISRA SHAHARAZ - Zahra, Siti; A’ida, Wanda Nur; Azam, Zidan Khairul; Nurholis, Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study investigates the use of exoticism in Qaisra Shahraz's novels The Holy Woman and Typhoon. Exoticism in literature extends beyond depicting foreign cultures, often functioning as a lens to critique social realities through stereotypes and cultural symbolism. This research employs a qualitative descriptive method, focusing on how Shahraz uses exotic elements to portray the complexity of gender, identity, and power dynamics in Pakistan. The study compares Shahraz’s works with Taj by Timeri N. Murari and Beneath a Marble Sky by John Shors, which showcase exoticism within Indian cultural contexts. The findings reveal that in The Holy Woman, exoticism highlights patriarchal traditions and social inequalities, particularly through rituals like making women "holy" to preserve family honor. Similarly, Typhoon explores dual identities and societal pressures within a diasporic setting, employing exotic cultural practices and language to enrich the narrative. Contrastingly, the Indian novels use the grandeur of the Mughal era, exemplified by the Taj Mahal, to critique political power struggles and social injustices. The study concludes that exoticism in these literary works serves as both an aesthetic device and a medium for social critique, revealing the nuanced intersection of tradition, gender, and power. This analysis enhances understanding of how postcolonial literature uses exoticism to navigate cross-cultural narratives and reflect on societal complexities.